Reduced agglomeration in solid propellants containing porous aluminum. (August 2014) - Yavor, Yinon; Rosenband, Valery; Gany, Alon
The effects of using porous aluminum particles in solid propellants were studied, with emphasis on the agglomeration phenomena. Burning strands containing either regular (as-received) or porous aluminum were photographed by a high-speed camera, and particulate combustion products were analyzed in a laser particle analyzer. Results obtained from experiments conducted in a pressure-range of 1–34 atmospheres show that porous aluminum particles produce smaller agglomerates than regular aluminum. The median diameter of agglomerates resulting from porous aluminum reached, on average, 70% of the one originating from regular aluminum. This reduction in agglomerate diameter corresponds to a substantial volume (and hence, mass) decrease of approximately 65%. It is assumed that the high-specific area of the porous aluminum particles (10–18 m 2 /g, similar to that of nano-Al) results in high reactivity, leading to shorter ignition time and hence to the formation of smaller agglomerates.